Role of intercellular communication between endothelial and stem cells in stemness and neurogenesis : focus on the soluble factor angiopoietin-1 and direct contact via lamimim-1/α6β1 integrin and connexin 43 as new targets for brain repair - Rosa, Alexandra Isabel Freitas (2011)
Tese de doutoramento em Medicina (Ciências Biomédicas), apresentado á Faculdade de Medicina da Universidade de Coimbra sob a orientação de João Malva e Catarina Resende de Oliveira.